Numerical modeling and experimental study of elastomer seal assembly in downhole wellbore equipment: Effect of material and chemical swelling. (September 2020) - Ahmed, Shawgi; Patel, Harshkumar; Salehi, Saeed
Abstract: Seal assemblies are critical elements in a variety of drilling and completion equipment such as wellhead casing hangers, packers, and liner hangers. Zonal isolation is accomplished by seal compression (energization) which generates contact pressure at the seal-pipe interface. The performance of a seal is evaluated based on its mechanical and hydraulic integrity as well as its resistance to failure mechanisms. Objective of this study is to evaluate the performance of a seal assembly at varying compressions, seal and pipe properties, and chemical swelling. In this paper, numerical modeling approach validated by a lab-scale experimental work has been presented. Finite element model and experimental setup consisting of liner, casing, compression plates, and elastomer seal are used. In the model, seal performance was evaluated in terms of contact pressure generated at seal-pipe interface. Experimental setup was used to verify the modelling results. In experiments, sealability was evaluated by injecting gas and observing leakage. Modelling results indicate that elastomer sealability is linearly dependent on amount of seal compression. Numerical model also demonstrated that pipe material can have notable impact on elastomer sealability. Simulation results show that seal-pipe friction has insignificant impact on seal performance. Exposure to surfactant caused volumetric swelling of investigated elastomer materials. Despite reduction in hardness, volumetric swelling was high enough to generate additional seal compression and provide improved sealability as demonstrated by model. Performance evaluation of liner hangers is considered a challenge for industry and regulators because of limited testing protocols, standards, or regulatory guidelines for evaluating this type of barrier system. Information generated in this work will help further advance performance evaluation and qualification guidelines for liner hanger seal assembly. Highlights: Finite element modeling of liner hanger seal assembly. Experimental setup to test seal assembly. Review of Sealing mechanisms and failure modes of liner hanger seal assembly. Parameters influencing contact pressure. Elastomer performance under chemical swelling.